Evaluation of early retinal changes in patients on long-term hydroxychloroquine using optical coherence tomography angiography - Huanhuan Zhao; Menglu Pan; Yaping Liu; Fangyue Cheng; Zongwen Shuai (SAGE Publishing, 2024)
Background: Connective tissue diseases (CTD), including systemic lupus erythematosus and rheumatoid arthritis (RA), have long been treated with hydroxychloroquine (HCQ). However, prolonged HCQ use poses a risk of adverse effects, particularly retinopathy. Objective: To detect early retinal changes assessed by optical coherence tomography angiography (OCTA) in CTD patients with long-term HCQ treatment and to explore the relationship between OCTA parameters and the concentrations of HCQ and its metabolites. Design: A cross-sectional study conducted from March 2020 to October 2021 at the First Affiliated Hospital of Anhui Medical University. Methods: The area and perimeter of the foveal avascular zone (FAZ), the thickness of the fovea and parafovea, and the vascular density of the superficial capillary plexus (SCP) and deep capillary plexus (DCP) in each area of the macula were measured by OCTA in 43 CTD patients treated with HCQ for over 6 months. Meantime, blood concentrations of HCQ and its metabolites were determined by high-performance liquid chromatography-tandem mass spectrometry, and the clinical documents of all 43 involved patients were collected. Results: There is no significant correlation between OCTA outcomes and the patient's age, disease duration, and weight-dependent dose. HCQ cumulative duration positively correlated with FAZ area and perimeter ( r  = 0.419, p  = 0.005 and r  = 0.407, p  = 0.007, respectively) and negatively correlated with the foveal vessel density in DCP ( r  = −0.378, p  = 0.012). HCQ cumulative dose had a positive correlation with FAZ area and perimeter ( r  = 0.445, p  = 0.003 and r  = 0.434, p  = 0.004, respectively) and had a negative correlation with foveal vessel density in SCP and DCP ( r  = −0.383, p  = 0.011 and r  = −0.424, p  = 0.005, respectively). OCTA outcomes did not correlate with HCQ and its metabolite concentrations. Conclusion: OCTA could be used to detect microvascular changes in the macula of CTD patients with long-term HCQ therapy. It was not found the concentrations of HCQ and its metabolites were associated with retinal vascular changes.